Re-submit the evaluation for additional work of waterproofing - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding re-submit the evaluation for additional work of waterproofing of BRACU new campus development project.